Resilience of the Photoreceptors in Posterior Multifocal Placoid Pigment Epitheliopathy Observed by Microperimetry over Time. (17th February 2022) - Scarinci, Fabio; Varano, Monica; Parravano, Mariacristina
ABSTRACT: Aims: To analyze the morphological and functional findings using microperimetry and optical coherence tomography angiography (OCTA) in patients with acute posterior multifocal placoid pigment epitheliopathy (APMPPE). Methods: This retrospective observational case series included four eyes of two patients with APMPPE. Best-corrected visual acuity range was from 20/20 to 20/250. Microperimetry and OCTA evaluation were obtained in the acute and healed phase. The OCTA images of the choriocapillaris were superimposed on the microperimetry map at the last visit. Results: The retinal sensitivity improved between the baseline and the last visit in three out of the four eyes. At resolution phase, OCTA revealed zones with choriocapillaris flow deficit, which were associated with points of reduced retinal sensitivity. Conclusions: Microperimetry allows for a better evaluation of the extent of the unhealed functional defect in eyes with AMPPE. The multimodal imaging showed that structural and functional findings were associated in the resolution phase.